The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4269/ajtmh.21-0297
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Rates and Beliefs toward COVID-19 Vaccination among the General Population of Pakistan: A Cross-Sectional Survey

Abstract: Developing countries like Pakistan have previously suffered from barriers to acceptance of vaccination by the public because of financial and belief barriers. This study aims to explore these beliefs and highlight concerns regarding vaccine hesitancy in the general population of Pakistan since they are a hindrance to an effective coronavirus disease-19 (COVID-19) immunization in the country. A cross-sectional study was performed involving 1,778 participants from all four provinces of Pakistan. Results from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
(35 reference statements)
1
28
0
Order By: Relevance
“…An online survey study conducted during January-February 2021, with 1778 participants showed an overall COVID-19 vaccine acceptance rate of 72%. 75 An earlier online study conducted during September-October 2020 with 883 respondents showed a similar acceptance rate of 70.8% for COVID-19 vaccination. 76 The acceptance rates were also close to those in the study by Solís Arce et al that used phone interviews in a sub-national sample (76.1% during July-September 2020, that declined to 66.5% during September-October 2020).…”
Section: Pakistanmentioning
confidence: 75%
“…An online survey study conducted during January-February 2021, with 1778 participants showed an overall COVID-19 vaccine acceptance rate of 72%. 75 An earlier online study conducted during September-October 2020 with 883 respondents showed a similar acceptance rate of 70.8% for COVID-19 vaccination. 76 The acceptance rates were also close to those in the study by Solís Arce et al that used phone interviews in a sub-national sample (76.1% during July-September 2020, that declined to 66.5% during September-October 2020).…”
Section: Pakistanmentioning
confidence: 75%
“…During the initial vaccination campaigns, varying degrees of vaccine hesitancy were reported across the globe given the diverse social and behavioral influences ( 18 ). Fear of the side effects, preconceived notions about the vaccine's ineffectiveness and belief in natural immunity were some of the leading causes of unwillingness to receive initial doses of the COVID- 19 vaccine ( 19 , 20 ). According to a cross-sectional study conducted in China ( 15 ), concerns regarding vaccine safety appeared to be a significant barrier to vaccination uptake, whereas, in Poland, side effects due to previous doses were a leading cause of hesitancy for boosters ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, arranging broadcast sessions with medical professionals can help by spreading awareness regarding the benefits of COVID-19 vaccines and demonstrating the minimal side effects that they may cause. The importance of this action is proved by a cross-sectional study performed in Pakistan which showed that 44% of their participants agreed to get vaccinated for COVID-19 if recommended by a physician [ 28 ].…”
Section: Recommendations For Changementioning
confidence: 99%